A comparative study of Muslim and English criminal law in the areas of theft, murder and rape / Aiznin Sairi Sulaiman - Sulaiman, Aiznin Sairi (Faculty of Law, 1984)
In this paper the writer has attempted to compare two of the widely used systems of law i.e the English law and Islamic law. This paper is however limited to certain crimes considered to be grave under both school of law. For instance this paper covers specifically the offences of theft, murder and rape. The substantive laws relating to these are laid down and compared. Because of the scarcity of legal materials on Islamic penal law, the writer is forced to rely on certain texts and as such could not give a more comprehensive View presented by the four great Imams of Islam. While the English position is abundantly clear for all one has to do is to delve into the numerous books available to locate the law but Islamic penal law suffers from lack of written materials on it. Most western writers either ignore it or is ignorant of it or give a prejudiced picture of it. Muslim writers too are equally guilty, materials on the subject of theft and rape are virtually non existent. Most of the law stated here were gleaned from various seminar papers and lectures presented by various members of the Islamic teaching profession? This project paper rests on the assumption that the reader posses some basic knowledge of Islam as a way of life and not me— rely as a religion.